Intra-Articular Application of Sluijter-Teixera Poisson Pulsed Radiofrequency in Symptomatic Patients with Knee Osteoarthritis: Focus upon Clinical Efficacy and Safety. (20th February 2021) - Filippiadis, D.; Tsochatzis, A.; Petsatodis, E.; Galanis, S.; Velonakis, G.; Giankoulof, C.; Kelekis, A.
Abstract : Purpose . To retrospectively evaluate the effectiveness of intra-articular application of Sluijter-Teixera Poisson pulsed radiofrequency (STP PRF) in knee osteoarthritis symptomatic patients with chronic pain refractory to conservative therapies. Materials and Methods . Institutional database research of two centers identified 39 cases of knee osteoarthritis patients treated with intra-articular STP PRF. Pain prior and one-week and one-, three-, six-, and twelve-month post-STP PRF was compared by means of a numeric visual scale (NVS) questionnaire. Cardiovascular and Interventional Radiological Society of Europe (CIRSE) classification system was used for complications reporting. Mean patient age was 71.59 ± 11.99 years, mean body mass index was 30.23 ± 4.69, and male/female ratio was 9/30. Results . Mean baseline pain score was 8.31 ± 1.70 NVS units. This was reduced to a mean value of 0.90 ± 1.50 NVS units one-week post-RF, 1.08 ± 1.53 at one month, 1.54 ± 1.88 at three months, 2.33 ± 2.17 at six months, and 3.23 ± 2.23 at 12 months of follow-up p < 0.01 . Pain decrease of more than 4 NVS units was noticed in 35/39 knees (89.7%) at first week, 36/39 knees (92.3%) at first month, 35/39 knees (89.7%) at three months, 32/39 knees (82.1%) at six months, and 25/39 knees (64.1%) at one year. There was no recurrence during the follow-up. No complication was observed. Conclusions . Percutaneous, intra-articular application of STP PRF is an effective and safe technique for chronic pain reduction in patients with knee osteoarthritis. Results seem to be reproducible and long lasting with significant patient satisfaction at 12-month follow-up.